SCHOOL VIOLENCE: PERSPECTIVES ON SOCIAL PERCEPTION AND THE APPLICATION OF LEGISLATION (CIPEEX, 2025)
School violence is configured as a social phenomenon of high complexity and relevance, directly impacting the daily routines of educational institutions, as well as the physical, psychological, and academic well-being of students, teachers, and other members of the school community. This study presents a curricular extension proposal developed by students and professors of the Law program at the Evangelical University of Goiás - Rubiataba Campus, structured in three stages: literature review on the subject, joint planning with the school community, and the implementation of a roundtable discussion in a full-time public school in the municipality of Rubiataba – GO, with the participation of teachers, coordinators, and the school management team. The objective was to identify the different manifestations of school violence, analyzing how the Federal Constitution of 1988, the Statute of the Child and Adolescent (ECA), and the Penal Code can serve as a foundation for the construction of preventive and repressive measures, as well as to discuss the importance of public policies aimed at protecting the school community and promoting an inclusive, welcoming, and safe environment. The methodological approach involved an interdisciplinary bibliographic survey in legal, social, and educational sources, articulated with participatory planning and the execution of the extension activity. The results indicated that episodes of physical, verbal, psychological aggressions, and even organized attacks in Brazilian schools have intensified the sense of insecurity, highlighting the need for greater integration between legislation, public policies, and pedagogical practices. The roundtable discussion made it possible to identify perceptions of the school community regarding the issue and contributed to strengthening dialogue as a coping strategy. It is concluded that the extension proposal played a significant role by integrating academic production and community practice, fostering debates capable of supporting new institutional and governmental actions aimed at ensuring security, respect, and the construction of peace within the educational environment.
Keywords: Insecurity; Legislation; Public policies; School violence